Design of a battery-operated portable DC power supply. Part 3 : system integration - Eng, Dawson Jun Wei (2018)
Portable battery has become a necessity in our daily life. Why is it so? Sole reason is due to the heavy usage of devices such as smartphones, tablets and notebooks which cause the internal battery to drain out faster. However, it has its own limitation such as it provides only a single voltage output with no adjustment required. This means that a user can only charge his device at a constant voltage usually around 2.1V. A battery operated DC power supply comes into play. It has many benefits such as the user can change its minimum/maximum voltages, prevent overcurrent and is smartly used. With such wondrous benefits, a full and precise integration is involved to ensure the success of the power supply. This report will involve the overall integration with an Arduino microcontroller. It acts as a watch point so as to oversee the entire integration. Hardware programmable IC/devices are used such as LCD, digital potentiometer and Bluetooth module.